English for Nurses: Needs Analysis and Syllabus - Tatiana Canziani (European Scientific Journal, ESJ, 2021)
In recent years, health profession degree courses entirely taught in English have become more and more frequent in Italy. Among these degree courses, the Associate Degree in Nursing has gradually spread in Italy since nursing is a profession that is highly required all over the world. As a matter of fact, Nursing is a profession that requires much specialized clinical competences and advanced communication skills (Schmidt 2003; Collins, 2005). From a linguistic standpoint, nurses have been defined as a sort of ‘communication broker’ (Bourhis et al., 1989) becoming linguistic mediators between doctors and patients (Garone & Van de Craen, 2017) since they have both to understand the doctor’s technical language and ‘translate’ it into the patient’s every day one. Thus, teachers face two main problems when designing an English course in Nursing: 1) the identification of student needs, which are technical and specific; 2) the development of a syllabus that considers the heterogeneous level of students who are quite often English native speakers. In this study, a syllabus designed for students attending the nursing degree course entirely taught in English at the University of Palermo based on the findings of the needs analysis will be proposed. Particular attention will be paid to the different communicative teaching strategies and techniques employed in order to help students to communicate more effectively in a clinical setting.